MEASURING AND ANALYZING THE IMPACT OF FDI IN DIVERSIFYING EXPORTS - THE OMANI ECONOMY, A CASE STUDY FOR THE PERIOD 2002-2022 - Salam Kazem Shani; Safaa Abdul Jabbar Ali; Taqi Abdul Redha Al Abdwani; Issa Sabeel Al Balushi (Scholars Digest Publishing, 2025)
For the years 2002–2022, this study looks at how FDI contributes to export diversification in the Omani economy. In order to diversify exports and lessen the negative effects of economic reliance on a single resource, several rentier economies have implemented certain tactics. One of the most important methods for accomplishing this objective is FDI (FDI), which effectively implements a targeted investment policy by focusing investments on economic sectors that support export diversification. We use advanced econometric analysis to find out how much foreign direct investment (FDI) affects exports of goods in the oil and gas sector and other sectors. We do this by using the Autoregressive Distributed Lag (ARDL) model. The data's most notable finding is that foreign direct investment (FDI) in the oil and gas production sector considerably increases exports in the short run. However, over time, exports are not greatly impacted by foreign direct investment (FDI) in the oil and gas production sector or in other economic sectors.
Keywords: Foreign Direct Investment (FDI), Economic Diversification, Export Diversification, Oil Exports, Non-Oil Exports.